2017
DOI: 10.1039/c7sc02294h
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer-free visible light-mediated gold-catalysed cis-difunctionalization of silyl-substituted alkynes

Abstract: A new photosensitizer-free visible light-mediated gold-catalysed cis-difunctionalization reaction is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 67 publications
3
57
1
Order By: Relevance
“…[289] The reaction is chemoand regioselective toward cis-substituted products rather than the more common trans-isomers. [289] The reaction is chemoand regioselective toward cis-substituted products rather than the more common trans-isomers.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…[289] The reaction is chemoand regioselective toward cis-substituted products rather than the more common trans-isomers. [289] The reaction is chemoand regioselective toward cis-substituted products rather than the more common trans-isomers.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…Controlled experiments, DFT calculations,a nd NMR and ESI-MS spectroscopic studies revealed that the reaction is initiated by as ingle-electron transfer (SET) at Au I .T he photoactivationo fa ryl diazonium salts will be followed by the addition of the in situ generated aryl radicalt ot he Au II intermediate, which would produce an Au III intermediate. (a) Photocatalyst-freed ualAua nd visible-light-promoted syn-difunctionalization of alkynes and (b) plausible mechanisms proposed by Deng et al [289] Scheme58. Finally,a facile reductive elimination process would lead to the crosscoupledp roduct.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[46] In 2017, the group of Wong used Ph 3 PAuCl as ac atalystt o describe an interesting cis-difunctionalizationo fs ilyl-substituted alkynes, which delivered silyl-substituted quinolizinium compounds under blue LEDs irradiation (Scheme 18 a). [47] Notably,t he reaction involved an unusual syn insertion and proceeded with high chemo-and regioselectivity.T he mechanism was studied by NMR spectroscopy,E SI-MS, and UV/Vis absorption. It wasf ound that whereas Ph 3 PAuCl did not absorb at l abs > 395 nm, the aryl diazonium salt presentedatail of the lowest energy absorption peak at l abs > 395 nm.…”
Section: Gold(i) Oxidation With Aryldiazonium Salts Assisted By Lightmentioning
confidence: 99%